2009
DOI: 10.1097/aln.0b013e31819b5d40
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Insertion Techniques of ProSeal™ Laryngeal Mask Airway

Abstract: The rotational technique is more successful than the standard technique and is associated with less pharyngeal mucosal trauma, as evidenced by a lower incidence of sore throat and mucosal bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 14 publications
3
67
0
1
Order By: Relevance
“…This success rate is consistent with previous reports, in which the primary success rate for i-gel insertion with the standard technique was 78-93% [8,10,17]. Our previous reports comparing two insertion techniques for the ProSeal LMA showed that the success rate at the first attempt was significantly higher in the rotation group than in the standard technique group [13][14][15], similar to the present study using the i-gel. Our findings suggest that the standard digital technique to insert supraglottic airway devices such as the i-gel or ProSeal LMA should be replaced with the rotational technique to increase the first-attempt insertion success rate.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This success rate is consistent with previous reports, in which the primary success rate for i-gel insertion with the standard technique was 78-93% [8,10,17]. Our previous reports comparing two insertion techniques for the ProSeal LMA showed that the success rate at the first attempt was significantly higher in the rotation group than in the standard technique group [13][14][15], similar to the present study using the i-gel. Our findings suggest that the standard digital technique to insert supraglottic airway devices such as the i-gel or ProSeal LMA should be replaced with the rotational technique to increase the first-attempt insertion success rate.…”
Section: Discussionsupporting
confidence: 93%
“…A recent case report showed that the reverse technique for i-gel insertion, with the device inserted into the mouth upside-down, may be useful to improve the insertion success rate when the first attempt by the standard technique fails [12]. Our previous studies demonstrated that the rotational technique provides a higher success rate at the first attempt with less pharyngeal mucosal trauma than the standard technique for insertion of the ProSeal TM laryngeal mask airway (LMA) [13][14][15]. To our knowledge, there have been no previous reports regarding the efficacy of the rotational technique for i-gel insertion.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, the rotation technique was associated with a higher success rate and less postoperative sore throat than the standard technique. 7 However, the study was limited to small-sized (size 3) PLMAs and women patients breathing spontaneously undergoing brief surgery. Larger sizes (size 4 or 5 for women and size 5 for men) are recommended to ensure a good seal and to allow positive pressure ventilation.…”
Section: Résumémentioning
confidence: 99%
“…A 90° rotation technique has been described, and it is more successful than the standard technique and is associated with less airway morbidity (12). It does not involve the use of additional introducer aids.…”
mentioning
confidence: 99%